Bullous systemic lupus erythematosus in a 16-year-old male patient - Aguilar García, Karla Fiorella (2022)
Bullous systemic lupus erythematosus (BSLE) is a vesiculobullous disease mediated by autoantibodies in patients with systemic lupus erythematosus (SLE). Tense vesicles and bullae are seen on an edematous, erythematous and sometimes normal skin in any body region, including mucous membranes and non-photoexposed areas. This is the case of a 16-year-old male patient with lupus nephritis who, on the seventh day of hospitalization, presented multiple serous and hemorrhagic blisters on the face, trunk, abdomen and upper extremities. The histological study showed a subepidermal bullousdermatosis with numerous neutrophils.